Characterization of Physical and Biological Properties of a Caries-Arresting Liquid Containing Copper Doped Bioglass Nanoparticles - Se-Jung Bang; Soo-Kyung Jun; Yu-Jin Kim; Jun-Yong Ahn; Huong Thu Vu; Nandin Mandakhbayar; Mi-Ran Han; Jun-Haeng Lee; Jong-Bin Kim; Jong-Soo Kim; Jonathan C. Knowles; Hye-Sung Kim; et al. (MDPI AG, 2022)
Silver diamine fluoride (SDF) is an outstanding dental material for arresting and preventing caries, but some drawbacks, such as high flowability due to low viscosity and cytotoxicity to the pulp, have been reported. To overcome these problems, copper-doped bioactive glass nanoparticles (CuBGns) were combined with SDF. After synthesis, CuBGns were examined by physical analysis and added in SDF at different weight/volume% (SDF@CuBGn). After assessing physical properties (viscosity and flowability) of SDF@CuBGn, physicochemical properties (morphology before and after simulated body fluid (SBF) immersion and ion release) of SDF@CuBGn-applied hydroxyapatite (HA) discs were evaluated. Biological properties were further evaluated by cytotoxicity test to pulp stem cells and antibacterial effect on cariogenic organisms (Streptococcus mutans and Staphylococcus aureus). Combining CuBGns in SDF increased the viscosity up to 3 times while lowering the flowability. More CuBGns and functional elements in SDF (Ag and F) were deposited on the HA substrate, even after SBF immersion test for 14 days, and they showed higher Cu, Ca, and Si release without changing F and Ag release. Cell viability test suggested lower cytotoxicity in SDF@CuBGn-applied HA, while CuBGns in SDF boosted antibacterial effect against S. aureus, ~27% in diameter of agar diffusion test. In conclusion, the addition of CuBGn to SDF enhances viscosity, Ag and F deposition, and antibacterial effects while reducing cell toxicity, highlighting the role of bioactive CuBGns for regulating physical and biological effects of dental materials.